Dari Perahu Sri Komala Hingga Puputan; Perlawanan terhadap Pemerintahan Hindia Belanda 1906 - Mirawati, Inna (Fakultas Ilmu Budaya, Universitas Diponegoro, 2013)
This research discusses the kingdom of Badung in Bali resistance against the Dutch that lasted six days, starting from December 15 until September 20, 1906. That event was known as Puputan. The main cause of this opposition stemmed from Sri Komala stranded boat on the beach of Sanur. The Dutch considered the king of Badung should responsibile towards this event. So this research entitle